2024
DOI: 10.2340/jphs.v59.19649
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of cost-effectiveness in breast reconstruction: deep inferior epigastric perforator flap vs. implant-based breast reconstruction

Emma Hansson,
Fredrik Brorson,
Jonas Löfstrand
et al.

Abstract: Background: There are several techniques for reconstructing breasts after mastectomy, but little scientific evidence for which technique is superior. The aim of this systematic review was to compare the cost-effectiveness of implant-based and autologous reconstruction and to evaluate the overall certainty of evidence, as well as the quality of reporting of the included studies. Methods: Studies investigating the cost-effectiveness of breast reconstruction with a deep inferior epigastric perforator (DIEP) flap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…A systematic review on health economics in breast reconstruction has demonstrated that there is no high-level evidence, regarding cost-effectiveness, to support recommendations and decisions in breast reconstruction. 8 The review 8 identified several methodological issues, such as a lack of a societal perspective, usage of standardised and validated methods to evaluate benefits, and modelling approaches not compatible with the reconstructive reality. The identified methodological weaknesses have formed the basis of the design of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review on health economics in breast reconstruction has demonstrated that there is no high-level evidence, regarding cost-effectiveness, to support recommendations and decisions in breast reconstruction. 8 The review 8 identified several methodological issues, such as a lack of a societal perspective, usage of standardised and validated methods to evaluate benefits, and modelling approaches not compatible with the reconstructive reality. The identified methodological weaknesses have formed the basis of the design of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the included studies were retrospective, non-randomised, did not correct for other factors that might affect satisfaction, and had a short follow-up. Moreover, few high-quality studies compare long-term cost-effectiveness 8 and the long-term need for revisions, corrections, and donor-site consequences. All of these factors are essential to create evidence-based guidelines, prioritise the usage of healthcare resources and to give the patients information on which they can base decisions of breast reconstruction.…”
Section: Introductionmentioning
confidence: 99%